The glass slipper and other stories - Yasuoka, Shotar (Dalkey Archive Press, 2008)
In addition to "The Glass Slipper," this collection contains eight other stories held together by a common thread of self-perception. Yasuoka writes from the belief that the self has such depths that at times it can appear to be illusory. Set against the chaotic backdrop of the era running from before World War II to just after its end, these stories are infused with a timeless sense of novelty and humor. (Book jacket)